Pengaruh Media Google Classroom terhadap Hasil Belajar Kognitif Siswa - Trisnawati, Lilis; Royani, Ida; Efendi, Ismail (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to determine the effect of google classroom media on cognitive learning outcomes of class X students of SMA Negeri 1 Batulayar for the academic year 2021/2022. The type of research used is a quasi-experimental research. The population in this study were all students of class X MIPA 1 Batulayar Academic Year 2021/2022 class X MIPA 1 Academic Year 2021 as a control class with a total of 24 people and class X MIPA 1 Academic Year 2022 as an experimental class with 20 students. Research data were taken from pre-test and post-test to both samples. The data collection technique used 15 multiple choice questions and 5 essay questions. Based on data analysis, the average value of the multiple choice pre-test experimental class 41, essay 23 and multiple choice pre-test control class 35.00, essay 14 with homogeneous categories and normally distributed. The results of the post-test showed that the experimental class average for multiple choice essays was 70 and 71.5 and the control class for multiple choice essays was 80.00 and 74.8. The final value data for the two classes was tested using the Critical one-tail t test, it was obtained tcount > ttable with a tcount of -4.00 and ttable of 1.685 at a significant level of 5%, so that Ha was accepted and Ho was rejected. It can be concluded that there is no influence of google classroom media on cognitive learning outcomes of class X students of SMA Negeri 1 Batulayar.